1981
DOI: 10.3109/01050398109076186
|View full text |Cite
|
Sign up to set email alerts
|

Threshold of Hearing by Bone ConductionA Contribution to International Standardization

Abstract: Threshold measurements with a Präcitronic KH 70 bone vibrator were carried out on 25 young, otologically normal subjects (50 ears) in the frequency range between 125 Hz and 8 000 Hz. The vibrator was applied to the human mastoid as well as to the forehead. The non-test ear was masked. Equivalent threshold force levels were determined on an artificial mastoid type B & K 4930. Between 125 Hz and 2 000 Hz, the equivalent threshold force levels for mastoid placement decrease steadily by about 13.5 dB/octave, they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…2 ), both the ipsilateral temporal region and mastoid showed lower BC thresholds by about 10 dB than stimulation at the forehead. These results correspond well with the findings by Richter and Brinkmann [1981] who described a difference between BC thresholds with forehead and mastoid stimulation of 1 11 dB. The American National Standards Institute (ANSI) has reported that adult behavioral thresholds measured with forehead stimulation are higher than those for mastoid placement of stimulation, by 14.0, 8.5, 11.5, 8.0 dB at 0.5, 1, 2, and 4 kHz, respectively.…”
Section: Subjective Bc Hearing Thresholdssupporting
confidence: 81%
See 1 more Smart Citation
“…2 ), both the ipsilateral temporal region and mastoid showed lower BC thresholds by about 10 dB than stimulation at the forehead. These results correspond well with the findings by Richter and Brinkmann [1981] who described a difference between BC thresholds with forehead and mastoid stimulation of 1 11 dB. The American National Standards Institute (ANSI) has reported that adult behavioral thresholds measured with forehead stimulation are higher than those for mastoid placement of stimulation, by 14.0, 8.5, 11.5, 8.0 dB at 0.5, 1, 2, and 4 kHz, respectively.…”
Section: Subjective Bc Hearing Thresholdssupporting
confidence: 81%
“…Similar findings were also shown in the work by Dunlap et al [1988] for dried cadaver heads, in the work by Stenfelt et al [2005] for heads from cadavers, and in the work by Durrant and Hyre [1993] for live subjects with normal hearing. Richter and Brinkmann [1981] showed that BC thresholds with stimulation at the ipsilateral mastoid were lower than BC thresholds with stimulation at the forehead for the conventional audiometric test frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…For the cranial midline location, the comparison of the SVIN SPV measured at the frontal location (Fz), vertex (Vx), bregma, occipital, and sub-occipital locations at 100 and 60 Hz in 15 UVL patients did not show significant differences (46). BCV applied to the frontal location is considerably less efficient than mastoid vibration in eliciting SVIN (26) and for vibration transfer to the promontory (54–56). …”
Section: Methods—practical Conditionsmentioning
confidence: 99%
“…Although the gain and output of BAHAs can be measured with the specially developed ''Skull Simulator'' [11], this was not appropriate for the present transcutaneous application. Instead, the ''Artificial mastoid'' was used [12]. Gain and maximum output were determined in a sound-field test setting with the conventional bone-conduction device (the Oticon E 300 P, tone in broad band position, output unlimited), plus the BAHA Classic and the BAHA Compact on headbands.…”
Section: Electro-acoustical Evaluationmentioning
confidence: 99%